Image-Guided Biopsy of Intracranial Lesions with a Small Robotic Device (iSYS1): A Prospective, Exploratory Pilot Study. Issue 4 (23rd January 2019) - Legnani, Federico G; Franzini, Andrea; Mattei, Luca; Saladino, Andrea; Casali, Cecilia; Prada, Francesco; Perin, Alessandro; Cojazzi, Vittoria; Saini, Marco; Kronreif, Gernot; Wolfsberger, Stefan; DiMeco, Francesco
Abstract: BACKGROUND: Robotic technologies have been used in the neurosurgical operating rooms for the last 30 yr. They have been adopted for several stereotactic applications and, particularly, image-guided biopsy of intracranial lesions which are not amenable for open surgical resection. OBJECTIVE: To assess feasibility, safety, accuracy, and diagnostic yield of robot-assisted frameless stereotactic brain biopsy with a recently introduced miniaturized device (iSYS1; Interventional Systems Medizintechnik GmbH, Kitzbühel, Austria), fixed to the Mayfield headholder by a jointed arm. METHODS: Clinical and surgical data of all patients undergoing frameless stereotactic biopsies using the iSYS1 robotized system from October 2016 to December 2017 have been prospectively collected and analyzed. Facial surface registration has been adopted for optical neuronavigation. RESULTS: Thirty-nine patients were included in the study. Neither mortality nor morbidity related to the surgical procedure performed with the robot was recorded. Diagnostic tissue samples were obtained in 38 out of 39 procedures (diagnostic yield per procedure was 97.4%). All patients received a definitive histological diagnosis. Mean target error was 1.06 mm (median 1 mm, range 0.1-4 mm). CONCLUSION: The frameless robotic iSYS1-assisted biopsy technique was determined to be feasible, safe, and accurate procedure; moreover, the diagnostic yield was high. The surface matching registration method with computed tomography as the reference image set did not negatively affect the accuracy of the procedure.